Dispersoid composition in zirconium containing Al-Zn-Mg-Cu (AA7010) aluminium alloy. (1st May 2019) - Cassell, A.M.; Robson, J.D.; Race, C.P.; Eggeman, A.; Hashimoto, T.; Besel, M.
Abstract: Zirconium (Zr) is used in modern aluminum alloys to form dispersoids that control grain structure. The interaction of these dispersoids with the alloying elements used to strengthen aluminum remains poorly understood. We have used high resolution imaging and composition analysis via electron microscopy to study the Zr-rich dispersoids in AA7010, a commercial Al-Zn-Mg-Cu alloy, addressing this knowledge gap. We show that the dispersoids are not of the ideal Al3 Zr stoichiometry, and contain Zn up to approximately 15 at%. Copper also concentrates in the dispersoids up to approximately 6 at%. Atomistic simulation was used to predict the partitioning, demonstrating favourable substitution of Zn and Cu onto the Al sublattice in the dispersoid phase, consistent with the measurements. We have also observed larger, facetted dispersoids, which are not of a phase observed in the binary Al–Zr system. Instead, we have found a previously unreported dispersoid structure (tI10 Ni4 Mo structure type), which we propose is stabilized by the presence of Zn. We have calculated the total loss in Zn and Cu due to partitioning into the dispersoids. We show this is too small to directly have a detrimental effect on age hardening, but may have a secondary effect in promoting heterogeneous nucleation for undesirable quench induced precipitation. Graphical abstract: Image 1